In vivo transcription of bacteriophage phi 29 DNA: transcription initiation sites. - Barthelemy, I (1986)
The initiation sites of the RNA transcripts synthesized in vivo in Bacillus subtilis infected with bacteriophage phi 29 have been mapped by S1 protection experiments. Nine transcription initiation sites were localized along the entire phi 29 genome, close to previously reported B. subtilis and Escherichia coli RNA polymerase-binding sites. Eight of these sites corresponded to early transcription and only one corresponded to late transcription. By using 5'-end-labeled RNA, four of the early sites and the late one were shown to be the main sites where initiation of transcription occurs in vivo in the phi 29 genome.